2017
DOI: 10.1007/jhep08(2017)048
|View full text |Cite
|
Sign up to set email alerts
|

Non-renormalization for non-supersymmetric black holes

Abstract: Abstract:We analyze large logarithmic corrections to 4D black hole entropy and relate them to the Weyl anomaly. We use duality to show that counter-terms in EinsteinMaxwell theory can be expressed in terms of geometry alone, with no dependence on matter terms. We analyze the two known N = 2 supersymmetric invariants for various non-supersymmetric black holes and find that both reduce to the Euler invariant. The c-anomaly therefore vanishes in these theories and the coefficient of the large logarithms becomes t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 74 publications
(175 reference statements)
3
31
0
Order By: Relevance
“…Although the focus in this paper has been on the non-extreme case, and specifically whether the logarithmic corrections to the black hole entropy depend on the departure from extremality, it is worth highlighting the extremal limit since in this special case a detailed microscopic model is the most realistic. In the extremal case we find the quantum correction on the non-BPS branch 22) for N = 6, 8. The surprising simplicity of this result is inspiring.…”
Section: Quantum Corrections To Black Hole Entropymentioning
confidence: 85%
See 1 more Smart Citation
“…Although the focus in this paper has been on the non-extreme case, and specifically whether the logarithmic corrections to the black hole entropy depend on the departure from extremality, it is worth highlighting the extremal limit since in this special case a detailed microscopic model is the most realistic. In the extremal case we find the quantum correction on the non-BPS branch 22) for N = 6, 8. The surprising simplicity of this result is inspiring.…”
Section: Quantum Corrections To Black Hole Entropymentioning
confidence: 85%
“…Conversely, our analysis shows that on the non-BPS branch c = 0 for N ≤ 4. On the BPS-branch not only has it been found that c = 0 for all N ≥ 2 but this fact has also been shown to be a consequence of N = 2 supersymmetry [22]. It would be interesting to similarly understand why c = 0 requires N ≥ 6 on the non-BPS branch.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, not all the solutions of the Einstein-Maxwell theory can be embedded in the Heterotic Superstring effective action because unequal electric and magnetic charges always generate a non-trivial scalar field. quantum black hole physics is currently attracting much attention [19,34,35,31,36,37,32,20,33,38]. A recurrent assumption in these explorations is that no additional degrees of freedom are activated at higher orders.…”
Section: Discussionmentioning
confidence: 99%
“…Bosonic sector: one graviton (g µν ), one graviphoton (A µ ) In this section, our motive is to briefly summarize a minimally coupled N = 2 supergravity embedded with the solutions of Einstein-Maxwell theory in four dimensions. There are a class of N = 2 supergravity solutions to the equations of motion, determined by certain conditions [45]. These conditions reduce the full N = 2 supergravity equations of motion to a much simpler form of equations of motion for Einstein-Maxwell theory.…”
Section: Physical Field Contentmentioning
confidence: 99%